2001
DOI: 10.1007/s005310000168
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis and its impact on Sr/Ca ratio in Holocene Acropora corals

Abstract: The effect of early diagenesis on Sr/Ca ratios encapsulated in coral skeletons was evaluated by comparing mineralogical, structural and geochemical characteristics of modern and Holocene, branching Acropora colonies. The modern specimens (Acropora danai, Acropora formosa) come from RØunion island (Western Indian Ocean) and the Great Barrier Reef of Australia respectively. The Sr/Ca ratios of modern specimens range from 9.08 to 9.37 mmol/mol. The fossil acroporids (Acropora group danai-robusta) were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The dissolution-recrystallization patterns observed in our Tridacnidae shells are similar to those observed in coral skeletons (e.g., Hendy et al, 2007;James, 1974;Rabier et al, 2008;Ribaud-Laurenti et al, 2001;Sorauf, 1980). For example, Sorauf (1980) noted that the "contact between aragonite crystals are etched," while Hendy et al (2007) reported that the ".…”
Section: Discussionmentioning
confidence: 52%
“…The dissolution-recrystallization patterns observed in our Tridacnidae shells are similar to those observed in coral skeletons (e.g., Hendy et al, 2007;James, 1974;Rabier et al, 2008;Ribaud-Laurenti et al, 2001;Sorauf, 1980). For example, Sorauf (1980) noted that the "contact between aragonite crystals are etched," while Hendy et al (2007) reported that the ".…”
Section: Discussionmentioning
confidence: 52%
“…Although some syntaxial cement becomes coarser than original coral aragonite biocrystals, and is thus identifiable based on texture, cements may mimic the original morphologies of the skeletal ultrastructure (Ribaud-Laurenti et al, 2001;Dalbeck et al, 2011) making it difficult to identify petrographically. Secondary, inorganic aragonite has an increased resistance to early diagenesis , potentially owing to its lack of associated organic matrix, and a reduced Mg/Ca ratio (Enmar et al, 2000;Sayani et al, 2011) compared to primary coral aragonite.…”
Section: Screening For Diagenesismentioning
confidence: 98%
“…Significant diagenetic alteration may occur even within the most recently deposited skeleton in the uppermost zone occupied by living tissue . The extent and timing of diagenetic alteration depend on the chemistry and volume of diagenetic fluid as mediated by porosity and permeability of the skeleton (Martin et al, 1986;Ribaud-Laurenti et al, 2001;Hendy et al, 2007) and the setting (e.g., living or dead coral; marine or meteoric environment). Skeletal porosity and permeability vary with taxonomy (Perrin and Cuif, 2001), which in turn controls skeletal ultrastructure (James, 1974;Perrin and Cuif, 2001), composition of intraskeletal organic matrices (Gautret, 2001) and the degree of associated bioerosion .…”
Section: Screening For Diagenesismentioning
confidence: 99%
“…Speleothems provide long records and are very useful for identifying general trends and maybe large 14 C production anomalies, but speleothems are potentially limited by the dating errors due to variable groundwater uranium-series and carbon chemistry. 230 Th/ 234 U/ 238 U dating of corals can be reasonably precise and accurate, but samples of appropriate age are hard to acquire and the coral 230 Th/ 234 U/ 238 U ages can be altered by freshwater diagenesis (Hamelin et al, 1991;Henderson et al, 1993;Gallup et al, 1994Gallup et al, , 2002Ribaud-Laurenti et al, 2001), and in some locations by marine cements (Ribaud-Laurenti et al, 2001;Paterne et al, 2004). Even trace amounts of diagenetic calcite deposited in subaerially exposed corals will bias the radiocarbon measurements (Chiu et al, 2005a).…”
Section: Radiocarbon Age Calibrationmentioning
confidence: 99%